Answer: The evaluations are done below.
Step-by-step explanation: We are given the following function :
![f(x)=3x^2-5x+7.](https://img.qammunity.org/2020/formulas/mathematics/college/oybmrxrqd3om4dxq3077npc7x4r4cibz2s.png)
We are to find the value of the following expressions :
![(A)~f(x+h)\\\\(B)~f(x+h)-f(x)\\\\(C)~(f(x+h)-f(x))/(h)](https://img.qammunity.org/2020/formulas/mathematics/college/9brzn68ooyee5p80mec9zkbw8m8q3g7uu8.png)
To find the above expressions, we must use the given value of f(x) as follows :
![(A)~\textup{We have}\\\\f(x+h)\\\\=3(x+h)^2-5(x+h)+7\\\\=3(x^2+2xh+h^2)-5x-5h+7\\\\=3x^2+6xh+3h^2-5x-5h+7.](https://img.qammunity.org/2020/formulas/mathematics/college/b7t2v55ual5wfo4ow7ytkckna1puu8d3dq.png)
![(B)~\textup{We have}\\\\f(x+h)-f(x)\\\\=(3x^2+6xh+3h^2-5x-5h+7)-(3x^2-5x+7)\\\\=6xh+3h^2-5h.](https://img.qammunity.org/2020/formulas/mathematics/college/npym37rbt4iqspqvy22lqosm9fctk1amrj.png)
![(C)~\textup{We have}\\\\(f(x+h)-f(x))/(h)\\\\\\=(6xh+3h^2-5h)/(h)\\\\\\=(h(6x+3h-5))/(h)\\\\=6x+3h-5.](https://img.qammunity.org/2020/formulas/mathematics/college/3tjhn6rksnggkezc70gxovc2kknfpgww1r.png)
Thus, all the expressions are evaluated.